Cancer risk assessment of personnel occupationally exposed to formaldehyde in a medical school - Pongsuteethavorn, Thiti; Krisorn, Phanumas; Choosong, Thitiworn; Chaiear, Naesinee (Journal of Medicine and Health Sciences, 2023)
Formaldehyde, a well-known human carcinogen in IARC Group 1, is used in various industries, with hospitals being one of the places that widely utilize it. Several medical staff members were exposed to a high concentration of formaldehyde. Therefore, this study aims to evaluate concentrations of formaldehyde exposure and cancer risk in medical staff. In this study, data were collected using the NIOSH 2016 method, applying personal sampling to medical staff during working hours for each job task. Then, this data was utilized to calculate cancer risk. Based on a sample size of 77 samples, the average formaldehyde concentration from the personal sampler was 0.0286 ppm, with the highest formaldehyde exposure being 0.0518 ppm during the teaching of gross anatomy and the lowest exposure being 0.0066 ppm in microscopic parasitology. The formaldehyde concentration was classified into high and low-exposure groups, where the high-exposure group included formaldehyde concentrations above 0.016 ppm. This group encompassed tasks such as teaching gross anatomy, embalming, injecting formaldehyde into cadavers, autopsy, and preparing gross anatomy class. The estimated lifetime cancer risk, as per US EPA guidelines, found that almost all medical staff had a potential cancer risk, except in microscopic and preparing parasitology, where the risk was deemed acceptable. In conclusion, medical staff exposed to formaldehyde should receive proper protection from exposure and undergo medical surveillance through annual physical examinations according to the risk.